Predictors of Recurrence and Survival in Cancer Patients With Pericardial Effusion Requiring Pericardiocentesis - Ahmed, Talha; Mouhayar, Elie; Song, Juhee; Koutroumpakis, Efstratios; Palaskas, Nicolas L.; Yusuf, Syed Wamique; Lopez-Mattei, Juan; Hassan, Saamir A.; Kim, Peter; Cilingiroglu, Mehmet; Marmagkiolis, Konstantinos; Vaporciyan, Ara A.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Aim This study investigated the factors predicting survival and the recurrence of pericardial effusion (PE) requiring pericardiocentesis (PCC) in patients with cancer. Materials and Methods We analyzed the data of patients who underwent PCC for large PEs from 2010 to 2020 at The University of Texas MD Anderson Cancer Center. The time to the first recurrent PE requiring PCC was the interval from the index PCC with pericardial drain placement to first recurrent PE requiring drainage (either repeated PCC or a pericardial window). Univariate and multivariate Fine-Gray models accounting for the competing risk of death were used to identify predictors of recurrent PE requiring drainage. Cox regression models were used to identify predictors of death. Results The study cohort included 418 patients with index PCC and pericardial drain placement, of whom 65 (16%) had recurrent PEs requiring drainage. The cumulative incidences of recurrent PE requiring drainage at 12 and 60 months were 15.0% and 15.6%, respectively. Younger age, anti-inflammatory medication use, and solid tumors were associated with an increased risk of recurrence of PE requiring drainage, and that echocardiographic evidence of tamponade at presentation and receipt of immunotherapy were associated with a decreased risk of recurrence. Factors predicting poor survival included older age, malignant effusion on cytology, non-use of anti-inflammatory agents, non-lymphoma cancers and primary lung cancer. Conclusion Among cancer patients with large PEs requiring drainage, young patients with solid tumors were more likely to experience recurrence, while elderly patients and those with lung cancer, malignant PE cytology, and non-use of anti-inflammatory agents showed worse survival.